High porosity reduced graphene oxide electrode prepared by langmuir-blodgett technique for application in bio-photovoltaics / Muhammad Musoddiq Jaafar - Muhammad Musoddiq , Jaafar (2017)
Traditional Langmuir-Blodgett (LB) method has proven versatile in fabrication of twodimensional (2D) film structures of thin films. This thesis meanwhile presents a study of developing three-dimensional (3D) structures of functional materials using unconventional LB methodologies. A detailed discussion of how 3D thin films of reduced Graphene Oxide (rGO) can be fabricated using dipping process post collapse pressure or breaking point, thus providing highly porous 3D surface topographies. Porosity could be optimized from nanometer to micrometer dimensions by varying the number of deposition with constant pressure. The 3D rGO thin film has been studied in applications for microbial fuel cells (MFCs) to provide improved biofilm formation and biocompatibility compared with the traditional 2D surfaces used as bioelectrodes. Furthermore, the inherent porosity of the deposited rGO films also improves the mass transport of materials; hence increase the charge-sustaining capacity and sensitivity. It was shown that the sixth deposition of rGO allowed the film to gain pore sizes between 1.2 to 3.8 μm, which is similar to the size of algae (2.0 – 3.5 μm). This feature of the rGO film accommodates an ideal surface for the anchoring of algae cells within the pores increasing surface contact and improves electron transfer efficiency. The rGO-algae thin film as electrodes in biophotovoltaic (BPV) systems have been studied and higher efficiency reported due to its intrinsic electrical properties and biological compatibility.